Myocardial deformation and twist mechanics in adults with metabolic syndrome: Impact of cumulative metabolic burden. (23rd August 2013) - Crendal, Edward; Walther, Guillaume; Vinet, Agnes; Dutheil, Frédéric; Naughton, Geraldine; Lesourd, Bruno; Chapier, Robert; Rupp, Thomas; Courteix, Daniel; Obert, Philippe
<x xml:space="preserve">Abstract</x> Objective The aim of the study is to characterize left ventricular (LV) myocardial mechanics in adults with metabolic syndrome (MetS), and elucidate the effects of multiple risk‐factors on myocardial function using speckle tracking echocardiography (STE); a more sensitive method than conventional echocardiography for detecting subclinical myocardial dysfunction. Design and Methods Cross‐sectional analyses of 92 adults (50–70 years) with MetS, and 50 healthy controls included conventional echocardiography, blood biochemistry, and STE‐derived myocardial longitudinal, circumferential, and twist mechanics. Results Using conventional measures, MetS participants revealed LV hypertrophy and reduced diastolic function compared with controls, while systolic function was preserved. From STE, MetS participants showed attenuated longitudinal strain (−16.8% ± 2.8% vs. −20.6% ± 2.7%), and both diastolic (1.1 ± 0.2 vs. 1.4 ± 0.3 s s−1) and systolic (−1.0 ± 0.1 vs. −1.2 ± 0.2 s s−1) strain rate (SR). Circumferential strain, SR, and twist mechanics did not differ. Participants with the highest number of MetS factors or diabetes demonstrated the greatest reduction in longitudinal strain and SR. Abdominal obesity, TNF‐α, HbA1c, and systolic dyssynchrony explained 48% of impairment in longitudinal strain. Conclusions Impaired longitudinal myocardial diastolic and systolic function, but preserved circumferential function and twist mechanics were found in MetS participants, indicative of altered subendocardial function. This dysfunction was best predicted by abdominal obesity, inflammation, glucose‐intolerance, and systolic dyssynchrony.